DEVELOPMENT OF RECOMMENDATIONS FOR EXTENDING THE USEFUL LIFE OF PASSENGER CARS - Myamlin, S. V.; Reidemeister, O. H.; Pulariia, A. L.; Kalashnyk, V. O. (Science and Transport Progress, 2015)
Purpose. The vast majority of passenger car fleet of «Ukrzaliznytsia» have cars with outlasted service life. In this regard there is a need to find methods to justify the extending useful life of passenger cars and to assess the car body frame residual life conformity to the operating load for the next life time. Methodology. The selection of cars enforced technical diagnostics of cars to detect the level of corrosion and mechanical damage. The following steps provided the car body frame strength analysis on the basis of experimental static and impact strength tests, the longitudinal force effect endurance tests as well as assessment and forecasting of conformity of car body operating life for the next period. Findings The car survey before testing showed that the technical condition of sleeper cars (SSC) is better than that of open-type cars (SOC). So, in SSC cars the thinning of the main load-bearing elements due to corrosion does not exceed 10%, there are no cracks, deformations, rack breakages, etc. At the same time in SOC cars the thinning due to local corrosion reached 35%. There are deformations and corrosion damage of side sill Zshape of both cars, single corner post breakages, damage to the joints of longitudinal tie rod and span bolsters. The conducted static and impact strength tests with following strength assessment of the car structural members showed that the strength of the latter is provided according to the normative documents, and these cars pose no threat to traffic safety. The impact endurance tests showed that all the cars passed the endurance tests without damage, which would prevent from testing and could not be removed during the next depot repair or overhaul, and had life length that allows them to extend the useful life for the next period. Originality. The results of experimental studies show that passenger cars after 28 … 30 and 33… 35 years of operation meet the requirements of strength and safety in accordance with regulatory documents and allow, provided the impact endurance, reasonable extending of the car service life. Practical value. The part of the car fleet, which was to be written off based on the service life, may extend lifespan without additional measures.